Staged Percutaneous Coronary Intervention with Rotational Atherectomy or Bypass Surgery in Chronic Hemodialysis and Severely Calcified Left Main True Bifurcation Lesion: A Case Report and Literature Review - Kazuhiro Dan; Akira Shinoda; Hector M Garcia-Garcia (Clinical Medicine Insights: Cardiology, 2020)
Previous observational studies and meta-analyses reported that the optimal strategy of coronary revascularization (percutaneous coronary intervention [PCI] and bypass surgery) for anatomically complex coronary artery lesions in the chronic hemodialysis setting is still controversial because the long-term outcomes were superior with coronary artery bypass grafting, especially with regard to repeat revascularization; however, short-term mortality with PCI was significantly lower because it is less invasive. Moreover, no guidelines show a strategy for this setting. We report the case of a patient with chronic dialysis and calcified left main true bifurcation lesion who underwent staged PCI with rotational atherectomy and minimally invasive direct coronary artery bypass for in-stent restenosis who died of non-occlusive mesenteric ischemia.